Cerebrospinal fluid biomarker levels are not affected by aspiration or gravity drip extraction methods in Alzheimer's disease: The AIBL study: Biomarkers (non‐neuroimaging): Method development and validation. (7th December 2020) - Doecke, James D; Francois, Cindy; Fowler, Christopher J; Stoops, Erik; Rainey‐Smith, Stephanie R; Li, Qiao‐Xin; Masters, Colin L; Martins, Ralph N; Villemagne, Victor LL; Vanderstichele, Hugo Marcel
Abstract: Background: Precise analysis of early changes in concentrations of proteins in cerebrospinal fluid (CSF) with qualified immunoassays can reflect the initiation or existence of Alzheimer's Disease (AD) pathology in brains of affected subjects. Although CSF biomarkers are well established nowadays for use in clinical routine worldwide (eg. NIA AA guideline, FDA qualifications), there is still some ambiguity as to which method should be used to extract the CSF. We aimed to compare in detail potential differences on the most promising protein biomarkers between gravity or aspiration extraction of CSF. Methods: Colorimetric ELISA immunoassays, developed by ADx NeuroSciences and commercialised by EUROMMUN, were used for the study. Our study assessed a panel of individual proteins (as well as their corresponding ratios) that are related to amyloidopathy (Aß1‐42, Aß1‐40), tauopathy (total tau), or synapse pathology (BACE1, Neurogranin Truncp75, a‐Synuclein). Concentration differences between using either gravity drip or aspiration extraction methods were evaluated in the same subjects in a sub‐population from the Australian Imaging, Biomarkers and Lifestyle (AIBL) study of ageing across. Subjects included in the study were cognitively normal (CN, N = 36), mild cognitive impairment (MCI, N = 8) or AD (N = 6). All analytes were tested by a single operator in parallel on the same day to minimize bias due to the test method and using manual test procedures. Results: Results from statistical assessments confirm high concordance in biomarker levels between extraction methods (Concordance Correlation [CC] >0.85). Bland Altman plot analyses revealed an even symmetry around the zero‐difference line for each of the individual biomarkers and their corresponding ratios. Passing Bablock regression defined low beta coefficients indicating high scalability. Results were consistent across all three cognitive groups, irrespective of sample size. Conclusions: The consistency in CSF biomarker levels across extraction methods demonstrates that the selection of the extraction method will not affect protein concentration analysis for respectively Aβ1‐42, Aβ1‐40, total tau, Neurogranin Truncp75, BACE‐1 and α‐synuclein). This new dataset will further help the field to better understand pre‐analytical factors of the discussed biomarkers, and prepare a final consensus guidance for collection, storage, and analysis of CSF.